2002
DOI: 10.1007/s100720200074
|View full text |Cite
|
Sign up to set email alerts
|

Modification of respiratory function parameters in patients with severe Parkinson's disease

Abstract: Respiratory dysfunction remains one of the most common causes of death in patients with complicated Parkinson's disease (PD). The aim of this study was to investigate pulmonary function in fluctuating PD patients during "on" and "off" states of the disease. We studied 12 fluctuating, non-smoking PD patients (H&Y stages 3-5) without a history of lung or cardiovascular disease; all patients underwent Hoehn and Yahr scale (H&Y) and Unified Parkinson Disease Rating Scale (UPDRS items 18-31) to evaluate extrapyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 0 publications
3
48
1
3
Order By: Relevance
“…16 The effect of levodopa on restrictive respiratory disease is controversial. some authors have shown an improvement in respiratory function after levodopa 13,14,16 whereas others did not. 17 These discrepancies may be due to differences in the patient's age, disease duration and severity and techniques used to assess respiratory function as well as the parameters measured.…”
Section: Restrictive Respiratory Dysfunctionmentioning
confidence: 95%
See 1 more Smart Citation
“…16 The effect of levodopa on restrictive respiratory disease is controversial. some authors have shown an improvement in respiratory function after levodopa 13,14,16 whereas others did not. 17 These discrepancies may be due to differences in the patient's age, disease duration and severity and techniques used to assess respiratory function as well as the parameters measured.…”
Section: Restrictive Respiratory Dysfunctionmentioning
confidence: 95%
“…since sabate et al in 1996, 6 higher incidences of restrictive respiratory disease have been observed in Pd patients [13][14][15] and a link between this and the motor manifestations of Pd has been described. a restrictive pattern has been shown to correlate with falls and freezing but not with tremor, rigidity or bradykinesia.…”
Section: Restrictive Respiratory Dysfunctionmentioning
confidence: 99%
“…A avaliação da função pulmonar por este método constitui-se num importante indicador da condição respiratória de pacientes com DP. (17) As medidas de Capacidade Vital (CV) e a Capacidade Vital Forçada (CVF), encontram-se abaixo dos valores teóricos preconizados em pacientes parkinsonianos, (8,17,18) e podem ser decorrentes da rigidez da musculatura da caixa torácica e da bradicinesia. (8) Observa-se que ao comparar a função pulmonar de indivíduos com e sem a doença de Parkinson, pessoas com a doença apresentam redução da CV e CVF.…”
Section: Discussionunclassified
“…Embora o uso da Levodopa seja o tratamento medicamentoso mais eficaz disponível para a doença de Parkinson, existem resultados divergentes. (18) Estudos evidenciaram a melhora sobre a função pulmonar após a administração da Levodopa, (17,23) com aumento nos valores dos parâmetros avaliados, a exemplo da CVF e do PFE (23) na fase on da medicação. Credita--se essa melhora à reversão parcial da deficiência motora, resultando em diminuição do tremor e rigidez muscular, melhora na coordenação dos mús-culos e facilitação do movimento.…”
Section: Discussionunclassified
“…When present, the most common patterns have been characterized as restrictive pulmonary dysfunction, obstructive airflow disease, and upper airway obstruction [1,[7][8][9][21][22][23][24]. Abnormal ventilatory control has also been described, even though respiratory flows and volumes were normal in most of the patients [25].…”
Section: Discussionmentioning
confidence: 99%